The diagnostic value of anti-neutrophil cytoplasmic antibody testing in a routine clinical setting. - McLaren, J; Stimson, R; McRorie, E; Coia, J; Luqmani, R (2001)
Anti-neutrophil cytoplasmic antibody (ANCA) tests are a routine clinical assay in most UK hospitals. We examined the role of routine ANCA testing in achieving a diagnosis of systemic vasculitis in a routine clinical setting. From April 1996 to March 2000, 2734 samples from five hospital departments were tested for ANCA by indirect immunofluorescence (IIF) at a single laboratory. After April 1999, enzyme-linked immunosorbent assays (ELISAs) were performed on all IIF-positive samples. Clinical diagnosis was determined for all patients with a positive IIF ANCA, and a sample of the ANCA-negative patients. Some 2-18% of patients with suspected ANCA-associated systemic vasculitis (AASV) had positive IIF ANCA. The AASV diagnosis was confirmed in 0-56% of these cases. Analysis by department suggested that 88-100% of patients with a positive IIF ANCA did not have AASV, except in the Rheumatology department. The positive predictive value (PPV) of IIF ANCA for AASV was 59% and the negative predictive value (NPV) was 84%. Of the patients with proven AASV, 41% did not have ANCA on IIF. Combined ANCA testing by IIF/ELISA had a higher sensitivity and PPV but lower specificity than IIF alone for AASV. For the combined IIF/ELISA test, only the Rheumatology department had a sensitivity or PPV >0% for AASV. The PPV of ANCA by IIF/ELISA for AASV was 79% and the NPV was 63%. The ANCA test is being widely applied with very poor return. Guidelines for more effective usage are proposed.